Elimination of neglected tropical diseases in the South-East Asia region of the World Health Organization - Jai P Narain; AP Dash; B Parnell; SK Bhattacharya; S Barua; R Bhatia; L Savioli (The World Health Organization, 2010)
The neglected tropical diseases (NTDs), which affect the very poor, pose a major public health problem in the South-East Asia Region of the World Health Organization (WHO). Although more than a dozen NTDs affect the region, over the past five years four of them in particular - leprosy, lymphatic filariasis, visceral leishmaniasis (kala-azar) and yaws - have been targeted for elimination. These four were selected for a number of reasons. First, they affect the WHO South-East Asia Region disproportionately. For example, every year around 67% of all new leprosy cases and 60% of all new cases of visceral leishmaniasis worldwide occur in countries of the region, where as many as 850 million inhabitants are at risk of contracting lymphatic filariasis. In addition, several epidemiological, technological and historical factors that are unique to the region make each of these four diseases amenable to elimination. Safe and effective tools and interventions to achieve these targets are available and concerted efforts to scale them up, singly or in an integrated manner, are likely to lead to success. The World Health Assembly and the WHO Regional Committee, through a series of resolutions, have already expressed regional and global commitments for the elimination of these diseases as public health problems. Such action is expected to have a quick and dramatic impact on poverty reduction and to contribute to the achievement of the Millennium Development Goals. This paper reviews the policy rationale for disease control in the WHO South-East Asia Region, the progress made so far, the lessons learnt along the way, and the remaining challenges and opportunities.